Value of Options in Airport Expansion - Example of AICM - Frederico Morgado; Sai Suresh Nagaralu; Rosário Macário; Richard De Neufville (European Regional Science Association (ERSA), 2011)
Investments decisions for airport capacity expansion are usually taken, either when demand exceeds the current capacity and the airport is working under congestion, or when current demand is expected to overcome current capacity sometime in the near future. In any case, decisions are taken taking into account forecasts of future demand. In many situations, deterministic analysis lead to a discouraging net present value (NPV) which in turn causes delays in the deciding process and eventually leads to further losses. This paper takes the Mexico City International Airport (AICM) as example, and performs an analysis of expansion investment, both in runways and terminals capacity, taking a perspective that is twofold: we take uncertainty of demand into account based on historical data of relevant parameters; we use flexibility in design by incorporating options in project, for both new runways and new terminal. Using a binomial lattice model, we calculate the value of options, perform sensitivity analysis and determine the expected statistical distribution of NPV. We obtain significant differences when compared with the deterministic perspective, and illustrate by example how real options and flexible design may dramatically improve the attractiveness of an investment decision.
Keywords: 330